Research and simulation of plastic zone around the Griffith’s crack (International Journal of Mathematics and Physics, 2015)
In this paper, by using the structural strength criterion of Neuber – Novozhilov, a formula of the critical load for plane blunt and sharp cracks is obtained. According to the obtained formula modeling of sharp crack as a thin ellipse with a ratio of small and major semi axes one to ten is carried out. With application of a software package OpenFOAM, based on the finite volume methods, by creating a solver for small elastoplastic deformation, we found the shape and size of plastic zone around the blunt and sharp cracks. A size of plastic zone based on calculation results satisfactorily agrees with the experimental data in researches of Hahn and Rosenfield, and shape – with data of Tuba. The results allow evaluating the impact of the microstructure to ductile material and on the behavior of structures made from such materials.